Effectiveness of Biodiversity Conservation Campaign Materials and Strategies in the Forest Ecosystem of Carranglan, Nueva Ecija, Philippines - Alberto, Roann P. (Silliman Journal, 2022)
This study was conducted to identify the effectiveness of different modes of campaign materials for the biodiversity conservation campaign in the forest ecosystem of Carranglan, Nueva Ecija, Philippines. Survey questionnaires were used to gather data such as demographic characteristics, mode, attributes, contents, and the respondents’ retention of the biodiversity campaign data. The data obtained in the study were analyzed descriptively. Frequency counts, percentages, and averages were computed. Likewise, graphical presentations were used for ease of describing and comparing the results of the study. All statistical analyses were performed using Statistical Package for the Social Sciences (SPSS). The print materials (posters, brochures, leaflets, pamphlets), collateral materials (eco-bags, shirts, pens, notebooks), seminarworkshops, field demonstrations, and social networks were identified as effective tools of campaign materials. However, posters were chosen to have the highest relevance, importance, and impact on biodiversity conservation campaigns, while brochures were considered the most cost-efficient and cheapest among all campaign materials.